Dampak Putaran Uruguay terhadap Industri Minyak Nabati - Wayan Reda Susila (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 1997)
The succes of the Uruguay Round was projected to have positive impacts on the edible oil industries although the impacts are not proportionally distributed. Edible oil procedures in Asia Pasific countries were projected to enjoy most of the gains,while most African countries which are net importers will suffer form prices increase. Commitments related to edibe oil trade in Uruguay Round will induce the incerase in price, production , consumption , and trade of edible oils 4.0 , 3.4 , 3.8 , and 11.6 percent , respectively. Moreover,palm oil producers such as Indonesia, was projected to be most beneficial from the trade liberalization of the edible oils.